Sociological analysis of the effectiveness of interactive methods that can be used to improve the quality of Education (Global Scientific Review, 2023)
The article highlighted the issues of identifying problems encountered in the process of applying interactive methods in improving the quality of education, identifying shortcomings in the professional competence of educators, analyzing the most effective of the selected interactive methods